2013
DOI: 10.1073/pnas.1308898110
|View full text |Cite
|
Sign up to set email alerts
|

Regulated structural transitions unleash the chaperone activity of αB-crystallin

Abstract: The small heat shock protein αB-crystallin is an oligomeric molecular chaperone that binds aggregation-prone proteins. As a component of the proteostasis system, it is associated with cataract, neurodegenerative diseases, and myopathies. The structural determinants for the regulation of its chaperone function are still largely elusive. Combining different experimental approaches, we show that phosphorylation-induced destabilization of intersubunit interactions mediated by the N-terminal domain (NTD) results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
174
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(179 citation statements)
references
References 70 publications
3
174
0
2
Order By: Relevance
“…Various studies have suggested that target protein binding is mediated by the N-terminal domain [95][96][97][98] or the ACD [99][100][101]. Indeed, with regards to the latter, we [18] and others [17,20,102] have shown that isolated ACDs exhibit chaperone function.…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 75%
See 3 more Smart Citations
“…Various studies have suggested that target protein binding is mediated by the N-terminal domain [95][96][97][98] or the ACD [99][100][101]. Indeed, with regards to the latter, we [18] and others [17,20,102] have shown that isolated ACDs exhibit chaperone function.…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 75%
“…Phosphorylation reduces the average oligomer size, and increases oligomeric polydispersity and rate of subunit exchange of αBc [98,[132][133][134], whereas it leads to a dramatic decrease in the size of Hsp27 oligomers, such that the triply phosphorylated isoform is predominately dimeric in solution [135,136]. Thus, under stress conditions, Hsp27 is phosphorylated, triggering dissociation of the high molecular mass Hsp27 oligomers [117,135,137,138] and an increase in the amount of exposed hydrophobicity on the newly formed Hsp27 dimers [139].…”
Section: Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Cdc37 wild-type and Cdc37 mutants were expressed in the E. coli strain HB101 as a His6-tagged version using a pQE30 vector containing the respective gene. Hsp90, Cdc37, Hop, Hdj1, and Hsp70 were expressed and purified as described (62)(63)(64).…”
Section: Methodsmentioning
confidence: 99%